ANALISIS FRAMING ROBERT ENTMAN PADA PEMBERITAAN LEDAKAN DI SMAN 72 JAKARTA OLEH KOMPAS.ID - Mila Audia Putri; Dormaulina Sitanggang (ADISAM PUBLISHER, 2025)
This study aims to examine how the online news outlet Kompas.id framed the explosion incident at SMAN 72 Jakarta in November 2025 and presented it to the wider public. Such coverage has the potential to influence public perceptions of school violence, adolescent mental health, and institutional responsibility. The research employs a qualitative method with a descriptive approach, using Robert Entman’s framing analysis model to analyze five news articles published by Kompas.id between 7 and 11 November 2025. The findings indicate that Kompas.id tends to frame the incident as a social crisis and a failure of character education systems rather than as an isolated criminal act. Each framing device emphasizes multifactorial causes, including revenge, bullying, and exposure to digital content, while promoting solutions centered on systemic prevention and professional mental health services. This framing approach encourages readers to pay greater attention to psychosocial factors, institutional accountability, and the importance of reforming character education to create a safe learning environment